Analysis of the Role of SARS-CoV-2 Infection on Clinical Superficial Mycosis: An Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Ariani, Tutty; Andriani Fuji Lestari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: The COVID-19 pandemic, caused by SARS-CoV-2 infection, has had multiple impacts on human health, including its potential influence on the manifestation and severity of skin diseases such as superficial mycoses. This study aims to analyze the relationship between SARS-CoV-2 infection and the clinical characteristics of superficial mycosis in patients at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This analytical observational study included 150 patients with laboratory-confirmed superficial mycoses. Demographic data, medical history, SARS-CoV-2 infection status (based on RT-PCR results), and clinical characteristics of superficial mycoses were collected and analyzed using SPSS software. Results: Of the 150 patients studied, 75 patients had a history of SARS-CoV-2 infection. No significant differences were found in the distribution of gender, age, and location of superficial mycosis infections between the groups of patients with and without SARS-CoV-2 infection. However, patients with a history of SARS-CoV-2 infection tended to have a higher severity of superficial mycosis (p < 0.05). In addition, there was a significant difference in the type of agent causing superficial mycosis between the two groups (p < 0.01). Conclusion: SARS-CoV-2 infection may influence the clinical manifestations of superficial mycoses, especially in terms of disease severity. These findings support the importance of monitoring and management of superficial mycoses in patients with a history of SARS-CoV-2 infection.